2018
DOI: 10.4172/2157-7110.1000716
|View full text |Cite
|
Sign up to set email alerts
|

Pre-harvest Modulation of N-3 Long-chain Polyunsaturated Fatty Acids in Rainbow Trout Meat for Human Consumption

Abstract: Since post-harvest improvement of food quality depends on the pre-harvest stage, controlling food quality at the pre-harvest stage is being recognized as an important aspect of food processing technology. n-3 Long-chain polyunsaturated fatty acids (n-3 LCPUFAs) are considered important factors in the suppression of cardiovascular disease and development of the infant brain and visual functions. Fish meat generally contains a larger amount of n-3 LCPUFAs than meat from terrestrial animals, but the amount of n-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…methionine and amino acid chelates) and enzymes (Apines-Amar et al, 2004;Hanini et al, 2013;Matsukura, Iino, Haga, Kitagima, & Satoh, 2017;Rodriguez-Estrada, Satoh, Haga, Fushimi, & Sweetman, 2009. Moreover, it has been suggested that dietary amino acid manipulation is an effective method of improving fillet quality in farmed fish (Yoshinaga, Ushio, Haga, & Satoh, 2018). Arginine is an amino acid, which is known to have functional roles and is considered as a potential supplement candidate.…”
mentioning
confidence: 99%
“…methionine and amino acid chelates) and enzymes (Apines-Amar et al, 2004;Hanini et al, 2013;Matsukura, Iino, Haga, Kitagima, & Satoh, 2017;Rodriguez-Estrada, Satoh, Haga, Fushimi, & Sweetman, 2009. Moreover, it has been suggested that dietary amino acid manipulation is an effective method of improving fillet quality in farmed fish (Yoshinaga, Ushio, Haga, & Satoh, 2018). Arginine is an amino acid, which is known to have functional roles and is considered as a potential supplement candidate.…”
mentioning
confidence: 99%
“…A study by Sun et al [ 53 ] showed that the residual stress present in the material is directly proportional to its strain energy. This strain energy ( ε ) can be expressed asε=12Gρb2$$\epsilon = \frac{1}{2} G \rho b^{2}$$where G is the shear modulus (26.1 × 10 3 MPa), b is the Burgers vector (0.286 nm), and ρ is the density of geometrically necessary dislocations, which can be calcualted using the equation below: [ 54 ] ραθbu$$\rho \approx \frac{\alpha \theta}{b u}$$where α = 3 is a constant corresponding to geometry of the boundary, u is the step size during the EBSD analysis (0.8 μm), θ is the average misorientation angle across the boundaries, which can be calculated asθ=β180Π$$\theta = \frac{\beta}{180} \Pi$$where β is the average KAM value. In this study, both the joints fractured at the Ti interface.…”
Section: Resultsmentioning
confidence: 99%